Giottus Pictor Band 2., Giottos Werke - Schwarz, Michael Viktor (2008)
This represents the second volume of a three-volume undertaking. Volume I (M.V. Schwarz und P. Theis, Giottos Leben (Giotto´s life), Vienna 2004) critically examined Giotto´s biography and the corpus of his documented works. Volume 2 presents these works in their respective contexts and attempts to gather information about dating and sequence.